Effects of porcine somatotropin and dietary lysine level on growth performance and carcass characteristics of finishing swine fed to 280 lb. - M E Johnston; B R Schricker; Jim L Nelssen; Robert D Goodband; Robert H Hines; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1990)
One hundred twenty barrows with an initial wt of 130 lb were utilized to determine the effects of dietary lysine level and porcine somatotropin (pST) injection on growth performance and carcass characteristics of finishing pigs fed to heavy market weights (280 lb). Pigs were injected daily in the extensor muscle of the neck with either 4 mg pST or a placebo and fed diets containing either .8, 1.0, 1.2, or 1.4% dietary lysine. Performance data were collected and evaluated for three weight ranges : 130 to 230 lb, 230 to 280 lb, and 130 to 280 lb. Two pigs from each pen were slaughtered to determine carcass measurements. The first pig was slaughtered at 230 lb and the second pig at 280 lb. Average daily gain (ADG) was maximized at the 1.0% lysine level for the pigs fed from 130 to 230 lb and for those fed from 130 to 280 lb. From 230 to 280 lb, ADG was improved for pigs fed the 1.0 and 1.4% lysine levels. Pigs injected with pST had a significant improvement in ADG compared to control pigs at all weight ranges. There was a linear decrease in average daily feed intake (ADFI) with increasing dietary lysine levels from 130 to 230 lb and from 130 to 280 lb. Feed conversion (F/G) improved as dietary lysine levels increased for pigs from 130 to 280 lb and was improved in response to pST-treatment. No pST x lysine interactions were observed for either ADG, ADFI, or F/G. Percent carcass muscle increased with increasing dietary lysine level and pST-treatment at both slaughter weights. A pST x lysine interaction was seen for percent muscle when pigs were slaughtered at 230 lb. Backfat thickness, kidney fat, and longissimus muscle area (LEA) were unaffected by dietary lysine level, but did show a pST response for pigs slaughtered at 230 lb. Longissimus muscle area was also increased with pST-treatment but was unchanged by changing lysine level for pigs killed at 280 lb. Kidney fat and backfat thickness decreased with pST-treatment and as lysine level increased in 280-lb pigs. There was no pST X lysine interaction at either slaughter weight for backfat thickness, kidney fat, or LEA. At slaughter weights of 230 and 280 Ib, there was an increase in trimmed ham weight with increasing dietary lysine level and pST-treatment, but no pST x lysine interaction. Organ weights were unaffected by lysine level, but were heavier with pST-treatment. These data indicate that growth performance was maximized at 1.0% dietary lysine, and carcass traits were optimized at dietary lysine of 1.2 to 1.4%. These results further demonstrate that pigs fed to 280 lb, when injected daily with pST, are more efficient, grow faster, and are leaner than control pigs.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Repartition; Lysine; GF; Performance; Carcass; Heavy; Weight